Minat Masyarakat Dalam Menabung Pada Masa Pandemi di BPRS Al-Washliyah Medan - Khoiriaturrahmah, Miftah; Dalimunte, Ahmad Amin (ISTIKHLAF: Jurnal Ekonomi, Perbankan dan Manajemen Syariah, 2021)
the results of this study indicate that; First, the public's interest in saving duringthe pandemic at BPRS Al-Washliyah Medan is interested in which the number of people has increased from the previous year. 5 components that influence people's interest in saving during the COVID-19 pandemic, namely: Attention, Interest, Trust (Disire), Confidence (Convication), Feelings of Happiness. Many people have barriers to income that is only enough for daily needs that cannot be set aside for savings. Second, the efforts made by the Bank to increase public interest during the COVID-19 Pandemic is the 4P Mix, namely Product, Price, Promotion, but socialization in shcools cannot be carried out because schools are carried out in a brave manner, not face-to-face as usual so it is difficult to socialize. Facing these problems, the Bank goes directly to the community to conduct promotions by complying with health protocols and conduct promotions throught the internet site. Keywords : Community, Saving, COVID-19, BPRS Al-Washliyah Medan